Effectiveness of Hexanoic Acid for the Management of Bacterial Spot on Tomato Caused by Xanthomonas perforans - Ketsira Pierre; Naweena Thapa; Qingchun Liu; Mustafa Ojonuba Jibrin; Jeffrey B. Jones; Shouan Zhang (Agriculture)
Bacterial spot of tomato (BST), caused by Xanthomonas euvesicatoria pv. perforans (referred to as X. perforans thereafter), is widely distributed globally, including Florida, and reduces fruit quality and yield in tomato fields. Currently, copper-based bactericides are widely used for this disease control; however, the effectiveness of these treatments has diminished due to the emergence of copper-tolerant strains. Therefore, there is a need for novel chemical controls against BST. In this study, we investigated hexanoic acid (HA) as an alternative against copper-tolerant strains of X. perforans through laboratory, greenhouse, and field experiments. In vitro experiments demonstrated HA had a lower minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) compared to copper sulfate, with values of 512 and 1024 mg/L for HA versus 1024 and 2048 mg/L for copper sulfate. HA exhibited bactericidal activity within 1 h at 512 and 1024 mg/L. In greenhouse trials, HA applied at 512 and 1024 mg/L two days before inoculation significantly reduced disease severity compared to untreated controls and Kocide 3000 (copper hydroxide) + Penncozeb. However, field trials indicated that while HA reduced disease severity relative to the untreated control, it did not outperform the grower standard commercial bactericide ManKocide (copper hydroxide + mancozeb), nor did it improve total yield. Previous studies have shown the antimicrobial activity of HA against various other phytopathogens, but this study is the first to demonstrate the potential of hexanoic acid for controlling BST.